Al-Wasaṭiyah Fī Al-Qur´ān Al-Karīm Min Khilāli Tafsīr ‘Abdur Rohmān Nāṣir As-Sa‘dī (Dirāsaħ Maudūiyyah): الوسطية في القرآن الكريم من خلال تفسير عبد الرحمن ناصر السعدي (دراسة موضوعية) - Muhammad Fathul Janan; Ammar Mohammed Abdo Al-Gumaei; Ahmad Haris (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD Cianjur, 2021)
This study aims to introduce the middle attitude or moderation in the Qur'an based on the thematic study of the Tafsir Abdul Rahman Nasser Al-Saadi on the verses of moderation in the Qur'an and the interpretation of the interpreters about the values contained in the meaning of moderation. The research method used is a thematic study of moderation verses in the Qur'an by collecting moderation verses and verses that are closely related to moderation values and then explaining them and analyzing them based on Abdul Rahman Al-Saadi's Tafsir Study. This study proves how important it is that a Muslim must instill in his soul the values of moderation or what we usually know as the middle of all kinds of affairs, be it in religious or world affairs with which a peaceful and prosperous life will be realized that will give birth to happiness in living this life.